1988
DOI: 10.1007/bf00254125
|View full text |Cite
|
Sign up to set email alerts
|

Toe temperature versus transcutaneous oxygen tension monitoring during acute circulatory failure

Abstract: Measurements of toe temperature and transcutaneous PO2 (PtcO2) have been both suggested for non-invasive assessment of peripheral blood flow in acute circulatory failure. The underlying principle of the two methods is that cutaneous vasoconstriction occurs early when tissue perfusion is altered. In 15 patients, we compared the two measurements during cardiogenic shock (27 measurements) or septic shock (29 measurements). Toe-ambiant temperature gradient and PtcO2 correlated well together (r = 0.66, p less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…11 These associations were further validated in later investigations of adult shock patients of mixed etiology 13,54,55 and postoperative patients, 28 although Vincent et al reported that associations present during cardiogenic shock were absent during septic shock. 55 Strong correlations between CPTG and cardiovascular status have also been found within pediatric settings. 12,35,51 Low temperature of the great toe, in conjunction with the temperature gradient between the peripheries and core or ambient temperature, have also been used as prognostic markers of survival.…”
Section: Evidence Supporting Skin Temperature Monitoring In Criticallmentioning
confidence: 92%
See 2 more Smart Citations
“…11 These associations were further validated in later investigations of adult shock patients of mixed etiology 13,54,55 and postoperative patients, 28 although Vincent et al reported that associations present during cardiogenic shock were absent during septic shock. 55 Strong correlations between CPTG and cardiovascular status have also been found within pediatric settings. 12,35,51 Low temperature of the great toe, in conjunction with the temperature gradient between the peripheries and core or ambient temperature, have also been used as prognostic markers of survival.…”
Section: Evidence Supporting Skin Temperature Monitoring In Criticallmentioning
confidence: 92%
“…Abnormal temperature gradients have been shown to persist in nonsurvivors yet normalise in survivors. 11,13,54,55 Separation of survivors from nonsurvivors has additionally been shown to be more likely using temperature gradients than cardiac index, 13 lactate, and arterial blood pressure 13,56 in acute myocardial infarction and shock patients, respectively. Abnormal temperature gradients have been shown to precede, or to occur simultaneously with, changes in hemodynamic parameters, including cardiac output, 10,28 demonstrating the value of monitoring skin temperature sequentially.…”
Section: Evidence Supporting Skin Temperature Monitoring In Criticallmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the practical application of these indices and the relationship with central hemodynamics or tissue oxygenation are not well studied. In adults with cardiogenic shock and in cardiac surgery patients, a crude correlation between central-to-toe temperature difference and cardiac output has been reported (14,23). In paediatric post-cardiac surgical patients, both capillary refill time and temperature gradients do not correlate well with the hemodynamic variables (13).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies demonstrated that a subjectively cool skin temperature was associated with a lower CO [31,32]. Studies evaluating the correlation between objective temperature measurements and CO showed conflicting results; some observed moderate correlations [33,35,40], whereas most observed no correlation [3438]. Skin temperature measurement methods differ widely and are likely influenced by several factors: age, ambient temperature, hypothermia, peripheral vascular disease, vasopressors, pain and anxiety have all been proposed as influencing circumstances [44,45].…”
Section: Univariable Studiesmentioning
confidence: 99%